RESEARCH PERFORMANCE PROFILE OF LPTK LECTURERS AS REFLECTION MATERIAL IN MATARAM CITY AREA - A. A Sukarso; Arifuddin Arifuddin; Edy Kurniawansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2022)
The need for scientific publications from the Government can encourage lecturers to improve the quality, quantity of research and scientific publications. In this regard, the purpose of this research is to explore the performance of lecturers in the field of research and scientific publications. This information can be used by stakeholders to conduct guidance on the performance of lecturers. This research is a descriptive-qualitative research conducted to identify the publication performance of LPTK lecturers in Mataram City. The research subjects were all LPTK lecturers in Mataram City. The data collection method used 2 main instruments, namely the Lecturer Publication Reflection Questionnaire and Interview Guidelines which were given specifically to Heads of Departments and Heads of Study Programs. This reflection questionnaire will provide information regarding the performance of lecturers' scientific publications during 2021. Meanwhile, interview guidelines are given to reflect on the performance of lecturers in depth. The results showed that the performance of lecturers was still quite low. Of the 10 study programs studied, 3 of them indicate that the quantity of international publications and ownership of IPR is still very low. From the results of the study, it can also be concluded that there is a need for activities such as international seminars to help lecturers to do international publications